Evidence of an IFN-γ by early life stress interaction in the regulation of amygdala reactivity to emotional stimuli. (December 2015) - Redlich, Ronny; Stacey, David; Opel, Nils; Grotegerd, Dominik; Dohm, Katharina; Kugel, Harald; Heindel, Walter; Arolt, Volker; Baune, Bernhard T.; Dannlowski, Udo
Highlights: This study investigated the influence of IFN-γ genotype on brain function using fMRI. IFN-γ genotype is involved with the regulation of amygdala reactivity to emotional stimuli. IFN-γ genotype moderates effects of early life stress on emotion processing. Abstract: Introduction: Since numerous studies have found that exposure to early life stress leads to increased peripheral inflammation and psychiatric disease, it is thought that peripheral immune activation precedes and possibly mediates the onset of stress-associated psychiatric disease. Despite early studies, IFNγ has received little attention relative to other inflammatory cytokines in the context of the pathophysiology of affective disorders. Neuroimaging endophenotypes have emerged recently as a promising means of elucidating these types of complex relationships including the modeling of the interaction between environmental factors and genetic predisposition. Here we investigate the GxE relationship between early-life stress and genetic variants of IFNγ on emotion processing. Methods: To investigate the impact of the relationship between genetic variants of IFNγ (rs1861494, rs2069718, rs2430561) and early life stress on emotion processing, a sample of healthy adults ( n = 409) undergoing an emotional faces paradigm in an fMRI study were genotyped and analysed. Information on early life stress was obtained via Childhood Trauma Questionnaire (CTQ). Results: A positive association between early life stress and amygdala reactivity was found. Specifically, the main effect of genotype of rs1861494 on amygdala reactivity indicates a higher neural response in C allele carriers compared to T homozygotes, while we did not find main effects of rs2069718 and rs2430561. Importantly, interaction analyses revealed a specific interaction between IFNγ genotype (rs1861494) and early life stress affecting amygdala reactivity to emotional faces, resulting from a positive association between CTQ scores and amygdala reactivity in C allele carriers while this association was absent in T homozygotes. Conclusions: Our findings indicate that firstly the genetic variant of IFNγ (rs1861494) is involved with the regulation of amygdala reactivity to emotional stimuli and secondly, that this genetic variant moderates effects of early life stress on emotion processing. These findings reiterate the importance that inflammatory genes play in the interaction with early life stress and the regulation of emotion processing.